A construção do processo de alfabetização na 1ª série - Rosemeire Reis Ribeiro da Costa (2005)
This work aims at understanding why in the same group, most of the students move forward in the understanding of the operation of the writing system, and a few in the initial levels of the evolving of writing. We tried to understand the literacy processs within it, as a process of acquisition of the alphabetical system, during the interaction between teacher-students in the clasroom of a group of first series of public school, located in boderline area of Belo Horizonte city. This research adopts an ethnografic methodology. During the observation, we were identified in the group some children who didn't move forward in the process of acquisition of the alphabetical system. It was noticed that the teacher's interventions in the classroom occurred based on the acquisition of the orthographic system. Once identified this problem, it was decided to investigate the process of learning of the system of the children's writing that sounded out of tune, in order to identify the referred lack for success them to reach in this process. The data analyzed of the research signaled that of literacy process has amoment to be finished, if a specific apprenticeship of the alphabetical system is expected. We understood that the teacher's mediation was sustained by an including conception of literacy. That conception diluted her specialty, given that she seemed not to have proportioned especif assistance to all those children who didnt understand the operation of the system, that is, the alphabetical base. Understanding literacy as the meaning of taking the acquisition of the alphabetical system, This rearch recognizes that there is a need to rethink the formation of the literacy teacher, starting from her own literacy conception.